B1 inhomogeneity correction of RARE MRI with transceive surface radiofrequency probes. Issue 5 (24th May 2020) - Delgado, Paula Ramos; Kuehne, Andre; Periquito, João S.; Millward, Jason M.; Pohlmann, Andreas; Waiczies, Sonia; Niendorf, Thoralf
Abstract : Purpose: The use of surface radiofrequency (RF) coils is common practice to boost sensitivity in (pre)clinical MRI. The number of transceive surface RF coils is rapidly growing due to the surge in cryogenically cooled RF technology and ultrahigh‐field MRI. Consequently, there is an increasing need for effective correction of the excitation field ( B 1 + ) inhomogeneity inherent in these coils. Retrospective B1 correction permits quantitative MRI, but this usually requires a pulse sequence‐specific analytical signal intensity (SI) equation. Such an equation is not available for fast spin‐echo (Rapid Acquisition with Relaxation Enhancement, RARE) MRI. Here we present, test, and validate retrospective B1 correction methods for RARE. Methods: We implemented the commonly used sensitivity correction and developed an empirical model‐based method and a hybrid combination of both. Tests and validations were performed with a cryogenically cooled RF probe and a single‐loop RF coil. Accuracy of SI quantification and T1 contrast were evaluated after correction. Results: The three described correction methods achieved dramatic improvements in B1 homogeneity and significantly improved SI quantification and T1 contrast, with mean SI errors reduced from >40% to >10% following correction in all cases. Upon correction, images of phantoms and mouse heads demonstrated homogeneity comparable to that of images acquired with a volume resonator. This was quantified by SI profile, SI ratio (error < 10%), and percentage of integral uniformity (PIU > 80% in vivo and ex vivo compared to PIU > 87% with the reference RF coil). Conclusion: This work demonstrates the efficacy of three B1 correction methods tailored for transceive surface RF probes and RARE MRI. The corrected images are suitable for quantification and show comparable results between the three methods, opening the way for T1 measurements and X‐nuclei quantification using surface transceiver RF coils. This approach is applicable to other MR techniques for which no analytical SI exists.